Characterisation of T cells induced by candidate conserved region HIV-1 vaccines in healthy HIV-1/2 negative volunteers - Ahmed, T; Tina Ahmed (2014)
HIV-1 has claimed the lives of millions of people globally and continues to spread despite development of highly active antiretroviral therapy. In 2013, 2.1 million new infections occurred and over 35 million people were living with HIV-1 infection. A prophylactic HIV-1 vaccine that can prevent infection or reduce viremia and subsequent transmission will always be an important part of the solution to bring this epidemic under control. In this thesis, the first HIV-1 vaccine candidate to focus on conserved regions of the virus (HIVconsv) was assessed in a phase I clinical trial conducted in healthy HIV-1/2 negative volunteers in Oxford. The HIVconsv T-cell immunogen was delivered using three leading vaccine modalities (DNA (D), modified vaccinia virus Ankara (M) and chimpanzee adenovirus serotype 63 (C)), in several novel heterologous prime-boost regimens. The frequency of T cells elicited through HIVconsv vaccination in the CM and DDDCM regimens surpassed that of previous HIV-1 cell-mediated vaccines. A large proportion of these T cells produced multiple cytokines and proliferated in response to recall peptides. The breadth of T-cell responses were also greater than the non-efficacious STEP study vaccine, with an average of 10 T-cell epitopes per vaccine recipient recognised across CM and DDDCM regimens. In vitro HIV-1 control mediated by CD8+ T cells was demonstrated for all vaccinees receiving the CM regimen, mainly against clade A (U455) and clade B (IIIB) isolates. Two vaccinees, demonstrated superior control of 6/8 and 7/8 viruses from the panel. The CM regimen induced significantly higher magnitudes of viral inhibition compared to the DDDCM or DDDMC regimens, with this regimen showing potential to overcome the disadvantage for subjects of carrying non-protective HLA alleles. Investigation of T-cell specificities revealed that the frequencies of T cells specific for conserved Gag but more so Pol regions significantly correlated with in vitro virus control. Direct examination of peptide expanded T-cell lines showed that all Pol pool- and limited Gag pool-specific cell lines reduced HIV-1 replication in vitro. In most individuals, targeting multiple HIV-1 epitopes concomitantly resulted in higher levels of virus inhibition than targeting a single viral epitope and two T-cell specificities showed enhanced control of HIV-1; the first within Pol (TAFTIPSI) and second from Gag (TERQANFL). These data support further development of the conserved region strategy for T-cell vaccines against HIV-1.